A comprehensive analysis of contact kinematics for planetary roller screw mechanism. (January 2023) - Xing, Mingcai; Zhang, Bohong; Deng, Pan; Xu, Jinquan; Cui, Yi
Abstract: In this work, a contact kinematic model of planetary roller screw mechanism (PRSM) is presented, and verified by comparing with published literatures. According to the conjugate surfaces contact condition and coordinate transformation, the sliding velocities in the screw-roller contact region and nut-roller contact region are calculated. It is proved that there is no relative sliding between roller and nut without geometry error. Furthermore, the effects of pitch circle mismatch error, geometrical and operating parameters of PRSM on the sliding velocities and sliding directions in the screw-roller and nut-roller contact regions are analyzed. It is found that the decreased pitch circle mismatch error, reasonable geometrical and operating parameters are conducive to improving the operation performance of PRSM. Highlights: A contact kinematic model of planetary roller screw mechanism is proposed. It is proved that there is no relative sliding on the nut-roller side without geometry error. The angular velocity of roller is calculated based on conjugate surfaces contact condition. The effects of pitch circle mismatch error, geometrical and operating parameters of PRSM on sliding velocities and sliding directions in contact regions are investigated.